Generealized Juvenile Demodicosis in Shih-Tzu Dog Successfully treated with Moxidectin - Waller, Stefanie Bressan; Versteg , Nielle; de Lima Wachholz, Peter; Pereira Dias, Tábata; de Araújo, Rebis; Brum Cleff, Marlete (Brazilian Journal of Case Reports, 2021)
Not applicable.